2020
DOI: 10.1097/rli.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT Findings in Patients With Coronavirus Disease 2019 and Its Relationship With Clinical Features

Abstract: Objectives: The aim of this study was to investigate the chest computed tomography (CT) findings in patients with confirmed coronavirus disease 2019 and to evaluate its relationship with clinical features. Materials and Methods: Study sample consisted of 80 patients diagnosed as COVID-19 from January to February 2020. The chest CT images and clinical data were reviewed, and the relationship between them was analyzed. Results: Totally, 80 patients diagnosed with COVID-19 were included. With regards to the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
538
11
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(639 citation statements)
references
References 17 publications
59
538
11
31
Order By: Relevance
“…This method made it much easier for us to assess the lesions. CT signs, GGO, consolidation, and fibrosis manifest differently over the course of the disease [21] and have different density ranges. This study shows that the proportion of consolidation increases with mean lesion density, and the proportion of GGOs, decreases with mean lesion density.…”
Section: Discussionmentioning
confidence: 99%
“…This method made it much easier for us to assess the lesions. CT signs, GGO, consolidation, and fibrosis manifest differently over the course of the disease [21] and have different density ranges. This study shows that the proportion of consolidation increases with mean lesion density, and the proportion of GGOs, decreases with mean lesion density.…”
Section: Discussionmentioning
confidence: 99%
“…The respective incidence rate of GGOs and consolidation are about 86% and 29% [15]. The most common morphology of these opacities are patchy and round ones, followed by triangular and linear ones [16,17]. The triangular or angular GGOs under the pleura with thickened internal interlobular septa is considered a new sign that one research paper has termed the "spider web" [17].…”
Section: Chest Ct Features Of Covid-19mentioning
confidence: 99%
“…The most common morphology of these opacities are patchy and round ones, followed by triangular and linear ones [16,17]. The triangular or angular GGOs under the pleura with thickened internal interlobular septa is considered a new sign that one research paper has termed the "spider web" [17]. Special classic signs, including "crazy paving" or "reverse halo", can also be seen, while cavitation, nodules, pleural effusions, and lymphadenopathy are rare.…”
Section: Chest Ct Features Of Covid-19mentioning
confidence: 99%
“…Based on these results, it can be suggested that the patients with the worst blood/ laboratory findings are also expected to have worse PII index values. 4,5 Finally, it is not surprising to find basal lung involvements (right or left), since ill patients would be less ambulatory and hence, likely to develop radiological changes in the dependent areas of the lungs. There are no studies focusing especially on immunocompromised patients, but it is expected that such patients are expected to develop more complications based on the previously established literature.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Similarly, Wu et al reported the dorsal segment of the right lower lobe (69/80 cases, 86%), a posterior basal segment of the right lower lobe (68/80 cases, 85%), and the lateral segment of the right lower lobe (64/80 cases, 80%) as the top 3 lung segments involved in their study. 4 As mentioned above, most studies found bilateral lung disease involvement.…”
mentioning
confidence: 92%